Analisis Layanan Digital Kependudukan Untuk Masyarakat Miskin di Kota Palembang Menggunakan Framework Information Technology Infrastructure Library (ITIL) - Reni Septiyanti; Darius Antoni; M Izman Herdiansyah; Widya Cholil (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
As it is known that the Government of Palembang has implemented e-government, but how much e-government can help the Palembang city government to interact between the government and all levels of society including the poor in the city of Palembang. In its application, the condition of e-government services is still insufficient infrastructure that supports                e-government services for the poor in palembang. To design a good e-government service, it is necessary to design SI/IT services for the community in Palembang with service design stages in the Framework Information Technology Infrastructure Library (ITIL) Version 2011 in order to be accepted in all levels of society including the poor in the city of Palembang. SI/IT service design based on the results of analysis of the condition and needs of SI/IT services to the business process of community service. This research uses qualitative approach method and analysis with reference standard approach using ITIL standard version 2011 in Service Design. The result of this research is in the form of the design of information system of digital service of population such as administration and population services, Family of Hope Program (PKH) services and digital archive storage services based on the Stages of Service Design in ITIL Version 2011 that has been done, namely the Service Level Management process in the form of Service Level Requirement, Service Level Agreement and Operational Level Agreement documents.